Formation of Advanced Nanomaterials by Gas-Phase Aggregation - Popok, Vladimir N.; Kylián, Ondřej (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The book represents a collection of papers from Special Issue "Formation of Advanced Nanomaterials by Gas-Phase Aggregation" published in journal Applied Nano. It contains review and original articles covering a range of topics on the growth of clusters/nanoparticles using gas-phase aggregation approaches, the application of cluster beams for the formation of nanomaterials with advanced properties and specific nanostructures as well as providing new fundamental insights on nanoscale properties of materials.